Activities Undertaken by the English Language Teachers for Professional Development - Bhandari, BhimLal (Journal of NELTA Gandaki, 2021)
The success of language learning and teaching mainly depends upon the professional activities that the teachers employ to improve job performance and provide appropriate input for better learning output in their students. By attending various workshop seminars and trainings, teachers update professional skills regularly and make their teaching career better and efficient. This study aimed at exploring the most common activities undertaken by the English language teachers for developing their professional skills. The study was carried out within the theoretical framework of social constructivism adopting narrative inquiry method to bring lived experiences of the participants. By using unstructured interview, I gathered information from two teacher participants teaching at secondary level in community schools in Butwal Sub-Metropolitan city, Rupandehi. The study revealed that the English language teachers were found attending conferences, trainings and workshop seminars, engaging in action research and academic writing for their professional development. However, poor internet access, lack of regular professional trainings and collaborative culture among them were the major challenges in teachers’ professional development. The study can contribute to improve the classroom pedagogy of the English language teachers and provide some insights to their knowledge and professional skills in the practices of various professional activities to be much more competent and skillful.